GDF-10 Induces an Inhibitory Effect on Epithelial-Mesenchymal Transition of Laryngeal Cancer via LPR4 - Kan, Xuan; Ai, Li; Guan, Ruidi; Hao, Jianwei; Sun, Yanan; Xiu, Wei (Current Pharmaceutical Design, 2023)
Background: Growth differentiation factor-10 (GDF-10), a member of the TGF-β superfamily, plays a crucial role in cell proliferation and differentiation. In some tumors, GDF-10 can act as a tumor suppressor to inhibit tumor progression, but its role in posterior squamous cell carcinoma has not been reported yet. Methods: The aim of this study was to investigate the effect of GDF-10 on the epithelial-mesenchymal transition of laryngeal squamous cell carcinoma, and to provide new ideas for future targets in the treatment of laryngeal squamous carcinoma. Results: The effect of GDF-10 on tumor growth was detected; bioinformatics analysis was performed to predict the downstream targets of GDF-10, and RT-PCR and western blot were performed to detect the expression levels of target genes and proteins, respectively. Conclusion: Our findings support that GDF-10 can inhibit the proliferation, migration, and invasion, and promote apoptosis of laryngeal carcinoma AMC-HN-8 cells. GDF-10 inhibits the EMT of laryngeal carcinoma through LRP4 and thus inhibits the progression of laryngeal carcinoma.
Keywords: EMT